The Current Status of Social Risks on Educational Systems. An Analysis Through Social Media - Peláez-Sánchez, José Ignacio; Vaccaro-Witt, Gustavo Fabian; Cabrera Lara, Francisco Elías (L. Gómez Chova, A. López Martínez, I. Candel Torres. IATED Academy, 2018)
Social Risk in education such as bullying, are usually invisible to teachers and parents, at all educational levels. However, these risks remain a reality everywhere in the world, turning into a problem that is rapidly globalizing due to the widespread access to the Internet. The Internet has permeated our entire society and is now present in almost every activity. The education and most aspects associated with it, such as Social Risks, are not exempt of this new form of communication within our society. This has led to a significant increase in damage Social Risks can exhort on the victims, due to several causes such as their capacity for dissemination, repetition and virality; greater anonymity of aggressors and the chance for more people joining them; continuity over time even when after school hours; display of intimacy before an endless crowd of people; ease of permanent control through geolocation, control of online statuses and connections; and even the risk of easily impersonating a victim. The first step to prevent these issues is to carry out a study on the current state of Social Risks. An updated snapshot would allow to draw up action plans based on reliable data and develop countermeasures to minimize the damage caused by current Social Risks to minors. The objective of this work is to conduct a study on unsolicited data obtained from Social Media on three of the most prominent Social Risks of our society, namely Bullying, Addictions and Xenophobia within the field of education, with the aim of obtaining an updated snapshot of their current status. The study was carried out during the second semester of 2017 and the first semester of 2018, quantifying the presence and emotion of said risks in Social Media, determining the most relevant terms, as well as the most used communication channels.
Este trabajo ha sido publicado en las actas del citado congreso, y revisados los documentos donde ha sido publicado, no se muestran impedimentos legales para que pueda ser publicado el documento.
Keywords: Exclusión social; Bullying en la escuela; Adicción; Social Risk; Education Challenges; Bullying; Addictions; Social Media